Perception of fragmented letters differentiates pathologically confirmed dementia with Lewy bodies from Alzheimer's disease: Language markers of early disease. (7th December 2020) - Salmon, David P.; Smirnov, Denis S.; Hamilton, Joanne M.; Hansen, Lawrence A.; Galasko, Doug R.
Abstract: Background: There is evidence that disproportionate impairment of visuoperceptual abilities can help distinguish Dementia with Lewy Bodies (DLB) from Alzheimer's Disease (AD), but the reliability of this effect has not been established in patients with autopsy confirmed disease, and the impact of co‐occurring Lewy body and Alzheimer pathology has not been examined. Method: A relatively pure test of visuoperceptual ability, the Fragmented Letters Task of the Visual Object and Space Perception (VSOP) battery was administered to 19 patients with pathologically confirmed DLB (17 Neocortical, 2 Limbic) with various levels of concomitant AD and 23 patients with pathologically confirmed AD only. Groups were matched for a mild level of dementia (MMSE >15, AD mean=24.7+3.6 and DLB mean=25.7+3.4) and were compared to 45 healthy elderly controls. In the Fragmented Letters Task individuals must identify 20 letters that are visually degraded by 70%. Performances on more complex visuospatial (Block Design) and memory (California Verbal Learning Test; CVLT) tests were also compared. Result: DLB patients performed worse than AD patients (B=‐2.29±0.64, p = 6x10 ‐4 ) and controls (B=‐2.73±0.62, p=3.8x10 ‐5 ) on the Fragmented Letters Task even after adjustment for demographics, MMSE, and ability to identify intact letters. AD patients did not differ from controls (B=‐0.53±0.62, p=0.34). Results were similar when DLB with (n=8, B=‐2.31±0.81, p = 0.006) or without (n=11, B=‐2.15±0.77, p = 0.006) concomitant AD pathology (Braak stage < 4 vs. 5‐6) were separately compared to pure AD. ROC analyses to distinguish DLB from AD showed that the Fragmented Letter Test (AUC 0.86) outperformed Block Design (AUC 0.71) and CVLT Immediate Recall (AUC 0.48). Conclusion: In contrast to complex visuospatial and memory tasks, a relatively pure test of visuoperceptual ability, the Fragmented Letters Task, was uniquely impaired in DLB ( vis a vis AD) and effective at distinguishing DLB from AD. Because impairment was not associated with concomitant AD pathology in DLB patients, and patients with AD were unimpaired, the deficit appears to be driven primarily by Lewy body pathology. Results suggest the quick and easily administered Fragmented Letters Task has excellent clinical utility for differentiating DLB from AD in mild to moderate stages of dementia.